If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-7=-33-2x
We move all terms to the left:
6x-7-(-33-2x)=0
We add all the numbers together, and all the variables
6x-(-2x-33)-7=0
We get rid of parentheses
6x+2x+33-7=0
We add all the numbers together, and all the variables
8x+26=0
We move all terms containing x to the left, all other terms to the right
8x=-26
x=-26/8
x=-3+1/4
| X+4x+500+2500=0 | | w=58=-2 | | r+48=95 | | 2x+17+3x-32=180 | | 3.5x-0.1666x=x+0.25 | | b-3.02=6.46 | | 2g=16.98 | | 5(x+2)-3(7-x)=5 | | (n-7)*8=72 | | (9n-6)*6=30 | | b+-18=-79 | | 1/2(x)-3=9 | | 4(x+5)*2(5-3x)=2 | | c+2=19 | | 3.35=b/4 | | r/3=4.23 | | |3x+9|=|4x-8| | | 5=c/2962 | | g+10=11 | | -5x+7=3x+11 | | x/7+11=9 | | 2^4x×2^(3-2x)=32 | | 2^4x×2^(3-2x)=32 | | b+b+50=180 | | 3.2=b+12 | | 254=s+30 | | (10-5x)-(8-4x)=x | | (9-10x)+21=8 | | 21+8y=-27 | | 0.08(4x-12)=0.32(1+x)-1.28 | | 5x+36=10-8x | | 45=4b=13 |